Endometrite citológica em vacas leiteiras mestiças e vacas de corte nelore : incidência e relação com o desempenho reprodutivo - Carneiro, Luísa Cunha (2011)
The aim of this study was to evaluate the incidence of cytological endometritis in crossbred dairy cows and Nelore beef cows and its impact to reproductive performance. In the first experiment were used 172 lactating crossbred cows (Holstein / Gir) between 32-70 days postpartum. All animals used had no history of retained placenta, clinical endometritis and had a body condition score (BCS) ≥ 2.50 (evaluated 1 - very thin to 5 - obese). The endometrial samples were collected by using the cytobrush method in which then, they were stained and examined microscopically. In the second experiment, were used 49 Nelore cows, between 29-90 days postpartum, under the same clinical conditions and BCS. The cytological samples were obtained by using the uterine lavage technique, and then, they were prepared and stained to be analyzed. In both experiments, cytological endometritis was considered with the presence of ≥ 5% neutrophils in each slide. Subsequently, all animals were submitted to artificial insemination (AI) and timed artificial insemination (TAI). In the first experiment, the incidence of cytological endometritis was 26%, and those cows with BCS ≤ 2.50 had a higher incidence of it, still, cows without endometritis, showed a pregnancy rate at 150 days postpartum higher. In the second experiment, the incidence was 22% and pregnancy rate at the end of the breeding season (BS) was higher in multiparous cows, however, the presence of cytological endometritis had no effect on conception rate or on pregnancy rate at the end of the BS.